Increasing awareness of radiation hazard and radiation protection among medical staff (Acta Scientiarum. Health Sciences, 2022)
The purpose of this study was to measure and increase the awareness of the risk of ionizing radiation and its protection among medical staff (non-radiological staff) at Najran region. This study was conducted in selected hospitals and health centers in the Najran region, for the medical staff (both gender, age: 22-60 years), as they were classified into four groups doctors, nurses, administrative staff, and workers, in which their data were collected through a distributed questionnaire. A two-stage questionnaire, where the first phase included their general awareness of the risks of ionizing radiation and its protection, while the second phase included measuring their awareness post the educational week that was held on September 26, 2020 - October 1, 2020. The general result of the study showed insufficient awareness of the risk of ionizing radiation and its protection among medical staff, adequate awareness increase after implementing the educational week, and the estimated rate of increasing their awareness by 90% in different gender and ages groups. The group of males and females between the ages of 22 and 30 recorded the highest participation and awareness at both pre and post-educational weeks compared to other groups.It is important to improve the level of knowledge and awareness regarding radiation hazards and radiation protection to prevent injuries among medical staff in hospitals.